2012
DOI: 10.1002/ptr.4593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grapefruit Juice and Ritonavir on Pharmacokinetics of Lopinavir in Wistar Rats

Abstract: Lopinavir (LPV), a newer HIV protease inhibitor, has poor bioavailability being a substrate of both cytochrome P450 3A enzyme system (CYP3A) and permeability-glycoprotein (P-gp). Ritonavir (RTV) is a known inhibitor of both P-gp and CYP3A and is co-administered with LPV in anti-HIV therapy. Grapefruit juice (GFJ) is known to inhibit CYP3A and has conflicting effects, ranging from activation to inhibition, on P-gp. In this research work, the effects of GFJ and RTV on the pharmacokinetics of LPV were compared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The lack of effect in the imatinib study could be attributed to the same reason a lack of effect was observed initially in the sirolimus study. A recent study in rats suggested that GFJ may be equally effective as ritonavir in increasing the bioavailability of the HIV protease inhibitor lopinavir (Ravi et al, 2012). Again, like the aforementioned studies, the GFJ was not analyzed for furanocoumarin content.…”
Section: Challenges In Establishing Clinical Significancementioning
confidence: 99%
“…The lack of effect in the imatinib study could be attributed to the same reason a lack of effect was observed initially in the sirolimus study. A recent study in rats suggested that GFJ may be equally effective as ritonavir in increasing the bioavailability of the HIV protease inhibitor lopinavir (Ravi et al, 2012). Again, like the aforementioned studies, the GFJ was not analyzed for furanocoumarin content.…”
Section: Challenges In Establishing Clinical Significancementioning
confidence: 99%
“…Major reason contributing to the high extraction of free LPV appears to be due to rapid metabolism of drug in liver. From the previously published literatures and our data, it is evident that any functional damage to liver would reduce LPV's clearance and could elevate drug plasma exposure.…”
Section: Discussionmentioning
confidence: 56%
“…It is an integral part of HAART regimen and a new standard of care for HIV‐infected patients . LPV shows poor plasma exposure after oral administration and high interpatient variability in humans due to its low aqueous solubility, extensive presystemic metabolism and P‐gp efflux . As a result, when given alone in conventional formulation (tablet and solution), it fails to achieve therapeutic concentration in blood and target viral reservoirs leading to a poor clinical outcome of the therapy …”
Section: Introductionmentioning
confidence: 99%
“…Low bioavailability and fast elimination are observed when lopinavir alone is orally administered; however, coadministration with ritonavir dramatically improves poor pharmacokinetic properties of lopinavir . Numerous studies demonstrated that ritonavir enhanced the transport of lopinavir from the intestinal lumen to the systemic circulation through inhibition of presystemic and systemic metabolism of lopinavir, which is a substrate of CYP3A . The findings form rationales for the therapy of HIV infection by lopinavir with a subtherapeutic dose of ritonavir, which results in increased and sustained plasma levels of lopinavir.…”
Section: Introductionmentioning
confidence: 99%